KOMPARASI PENDIDIKAN ISLAM PERSPEKTIF BUYA HAMKA DAN PENDIDIKAN ISLAM DI NEGARA TURKI - Susanti, Cela Petty; Valhani, Salwamia; Novitasari, Sherly Dian; Ayudiyanti, Putri Adinda (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Education is crucial in living the life cycle; the education that Buya Hamka affirmed has a deep understanding, is full of skill, and is oriented towards educational goals that are not always vertical. Unlike the Turkish state, education is more secular and modern. Based on the discussion of these comparisons, this study aims to uncover the Islamic education, Buya Hamka’s perspective, and Islamic education that exist in the country of Turkey. This research method uses library research with related books and journals. The results of this study show that Buya Hamka sees Islamic education as an attempt to understand the teachings of religion holistically and emphasises character education to form a qualified generation. On the other side, Turkey has an Islamic educational system that integrates general education as well as moral education. Islamic education between Buya Hamka and Turkey had the same purpose of forming a generation of noble and knowledgeable Muslims as well as building a civilised society for social development. This research provides a more comprehensive understanding of Islamic education in different territories of the country but has the same goal of informing Muslims of karimah morality.